The Influence of Non-Cash Payment Transactions on Economic Growth in 5 ASEAN Countries - Ferra, Yesi; Ajija , Shochrul Rohmatul (Jurnal Ilmu Ekonomi Terapan, 2023)
Technological advances are currently growing rapidly, financial technology is no exception. The development of financial technology has had an impact on innovation in the payment system from a cash payment system to a non-cash payment system. The purpose of this study was to determine the effect of non-cash payment transactions on economic growth in 5 ASEAN countries. The variable of economic growth in this study is calculated through the growth of real GDP published by the World Bank (WDI), and the variable of non-cash payments in this study is assumed to be through the growth of the transaction value of debit cards, credit cards, e-money and cheques issued by the Bank International of Settlement (BIS). The data used in this study is secondary data in the form of panels (annual) in 5 ASEAN countries from 2012 to 2019. The analytical method used in this study is the panel data regression method. The results of this study indicate that the growth in the value of non-cash payment transactions in the form of debit cards and e-money has proven to be able to stimulate economic growth in these countries. Meanwhile, payments by credit cards and cheques had no impact on economic growth. This is because debit cards provide direct access to consumers personal funds, making it easier for the public to consume goods and can also contribute to economic growth. As an electronic payment instrument, e-money has also been proven to provide benefits for alternative payments, especially for micro and retail payments. Through the use of e-money, the goverment's income can increase from the increasing number of customers who have used e-money payments, so that this can encourage an increase in economic growth.